PRAKTIK PENGELOLAAN KEUANGAN DESA DI DESA CURUGLEMO KECAMATAN MANDALAWANGI KABUPATEN PANDEGLANG TAHUN 2022 - Iin Sobirin; Mohammad Gazali; Kumba Digdowiseiso (LPPM Institut Pendidikan Nusantara Global, 2023)
The village is the smallest government structure in a country. Home Affairs Minister No. 20 of 2018 states, Village is a legal community unit that has regional boundaries that are authorized to regulate and manage government affairs, local community interests based on community initiatives, origin rights, and/or traditional rights that are recognized and respected in the system of government of the Unitary State. Republic of Indonesia. This study aims to explain the application of village fund financial management. The method used is a case study through interviews with residents and leaders of Curuglemo Village, Mandalawangi District, Pandelang Regency. This study found that village financial management in general was in accordance with applicable regulations. In addition, the Curuglemo Village Fund in 2022 will receive funds of Rp. 1, 498,330,000. The funds are used for administering village governance, village development, village development, community empowerment and are used in the areas of disaster management, emergency and village urgency.